Measurement of charged-particle spectra in Pb+Pb collisions at sqrt(sNN) = 2.76 TeV with the ATLAS detector at the LHC - Aad, G. (2015)
Charged-particle spectra obtained in Pb+Pb interactions at √ sNN = 2.76 TeV and pp interactions at √ s = 2.76 TeV with the ATLAS detector at the LHC are presented, using data with integrated luminosities of 0.15 nb−1 and 4.2 pb−1 , respectively, in a wide transverse momentum (0.5 < pT < 150 GeV) and pseudorapidity (|η| < 2) range. For Pb+Pb collisions, the spectra are presented as a function of collision centrality, which is determined by the response of the forward calorimeters located on both sides of the interaction point. The nuclear modification factors RAA and RCP are presented in detail as a function of centrality, pT and η. They show a distinct pT-dependence with a pronounced minimum at about 7 GeV. Above 60 GeV, RAA is consistent with a plateau at a centrality-dependent value, within the uncertainties. The value is 0.55 ± 0.01(stat.) ± 0.04(syst.) in the most central collisions. The RAA distribution is consistent with flat |η| dependence over the whole transverse momentum range in all centrality classes